KISAH-KISAH TRADISIONAL JAWA BARAT DALAM MEDIUM KOMUNIKASI VERBAL: KISAH-KISAH TRADISIONAL JAWA BARAT DALAM MEDIUM KOMUNIKASI VERBAL - Darsa, Undang; Permana, Rangga; Sumarlina, Elis (PT. RANESS MEDIA RANCAGE, 2023)
West Java is one of Indonesia's provinces with a wealth of literacy, including traditional tales dating back to prehistoric times. Over time, not only were these tales told orally, but they were also written down and published through various communication channels. From a communication perspective, verbal communication includes the oral and written transmission of messages from sources to recipients. Verbal communication is a form of communication that involves the use of spoken or written language. Traditional Sundanese oral and written narratives illustrate the instrumental and social functions of verbal communication. This study seeks to identify the traditional Sundanese tales, their classification into oral and/or written traditions, and the time period in which these tales first appeared. Authors collects data and conceptions regarding traditional Sundanese stories and verbal communication using a descriptive-qualitative methodology. The findings indicate that, from a communication standpoint, traditional Sundanese tales that have existed since prehistoric times can be classified as verbal communication, as these tales take the form of both oral and written communication. Oral Sundanese traditional tales are known as Carita Pantun, while written Sundanese traditional tales are manuscripts originating from mandala, Islamic boarding institutions, and schools. These traditional Sundanese tales are separated into five eras: prehistoric, regal, sultanate, colonial, and independence. From a communication standpoint, these traditional tales are a means of conveying events or phenomena that may have occurred in the past, as well as a means of cultural transmission from progenitors to descendants.